Advances in dataflow programming languages. - Johnston, Wesley M.; Hanna, J.R. Paul.; Millar, Richard J.
Many developments have taken place within dataflow programming languages in the past decade. In particular, there has been a great deal of activity and advancement in the field of dataflow visual programming languages. The motivation for this article is to review the content of these recent developments and how they came about. It is supported by an initial review of dataflow programming in the 1970s and 1980s that led to current topics of research. It then discusses how dataflow programming evolved toward a hybrid von Neumann dataflow formulation, and adopted a more coarse-grained approach. Recent trends toward dataflow visual programming languages are then discussed with reference to key graphical dataflow languages and their development environments. Finally, the article details four key open topics in dataflow programming languages.
Keywords: Dataflow; Co-ordination languages; Component software; Dataflow visual programming; Graphical programming; Multithreading; Software Engineering